A pilot-scale coupling of ozonation and biodegradation of 2, 4-dichlorophenol-containing wastewater: The effect of biomass acclimation towards chlorophenol and intermediate ozonation products. (10th September 2017) - Van Aken, Pieter; Van den Broeck, Rob; Degrève, Jan; Dewil, Raf
Abstract: The effect of pre-ozonation of a synthetic wastewater spiked with 2, 4-dichlorophenol prior to a biological treatment was investigated experimentally by using a pilot-scale bioreactor. The pre-ozonated wastewater was characterized by a brown color, probably due to the formation of typical intermediate products such as quinones or their derivatives. Because also under steady conditions a brown effluent of the bioreactor was observed, accompanied with an increased chemical oxygen demand of the effluent, it was assumed that the intermediate products were not completely biodegradable. However, a decreasing sludge volume index indicated the enhanced sludge settleability. Without pre-treatment, the complete biodegradation of 2, 4-dichlorophenol occurred. However, due to the presence of small particles, the effluent was not clear, even not after centrifugation. Moreover, the higher sludge volume index indicated the hampered settling of the sludge. Under both investigated circumstances, the nitrification and denitrification process was not affected. Graphical abstract: Highlights: The degradation of 2, 4-dichlorophenol was achieved, even without pre-ozonation. The sludge settleability was improved by ozonation of 2, 4-dichlorophenol. The sludge settleability was hampered when 2, 4-dichlorophenol was not pre-treated.